Этические проблемы современной науки - Смоляга, Марина Витальевна; Старикова, Г. Г. (НТУ "ХПИ", 2012)
В статье анализируется проблема взаимосвязей этики и науки. Рассматриваются особенности науки как системы знаний и как специфической формы человеческой деятельности. Особое внимание уделяется таким аспектам проблемы, как нравственная оценка целей, средств и условий научной деятельности.

This article is devoted to the problem of connection between the ethic and science. The specials of science as a system of knowledge and as a special form of the human action is analysed. The especially attention is given to the such problems as the moral appreciation of the aims, means and the provided of the science action.
Ethical problems of modern science
Keywords: ценности; система знаний; человеческая деятельность; нравственная оценка целей; ethics; science; values